BSIM-bulk MOSFET model for IC design : digital, analog, RF and high-voltage /: digital, analog, RF and high-voltage. (2023) - Hu, Chenming; Agarwal, Harshit; Gupta, Chetna; Chauhan, Yogesh Singh
No abstract available